One Day One Ayat Religious Culture as a Strategy for Strengthening Islamic Character Education in Schools - Muhamad Abdilah; Mahmutarom Mahmutarom; Sari Hernawati (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The rapid development of the digital era has created significant challenges for students’ moral and character development, including declining discipline, weakening spirituality, and increasing negative social behavior within school environments. In response to these challenges, schools are required to develop sustainable religious culture programs to strengthen Islamic character education. This study aims to analyze the implementation of the One Day One Ayat program as a religious culture strategy for strengthening Islamic character education at MAN 1 Ngawi. The study employed a qualitative case study approach involving 15 informants consisting of school leaders, Islamic Education teachers, homeroom teachers, and students. Data were collected through interviews, participatory observation, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the One Day One Ayat program was systematically implemented through daily Qur’anic habituation activities involving approximately 320 students. Observation findings indicated improvements in students’ punctuality, participation in collective worship, responsibility in completing academic tasks, consistency in Qur’anic memorization, and respectful interaction toward teachers and peers. Documentation records further showed active student participation in daily Qur’anic recitation and religious activities within the madrasa environment. The study also found that continuous habituation, teacher role modeling, and the integration of Qur’anic values into school activities contributed to strengthening students’ discipline, spirituality, moral awareness, and positive social behavior. This study concludes that the One Day One Ayat program represents an effective and sustainable religious culture strategy for strengthening Islamic character education in contemporary educational settings.